2010
DOI: 10.1684/epd.2010.0325
|View full text |Cite
|
Sign up to set email alerts
|

Study of cardiac autonomic function in drug‐naïve, newly diagnosed epilepsy patients

Abstract: Background. Epilepsy is associated with ictal autonomic dysfunction which may extend into the inter-ictal period. Antiepileptic drugs have often been blamed for cardiac autonomic dysfunction in epilepsy patients. In this study we have investigated cardiac autonomic parameters in order to evaluate autonomic functions of drug-naïve epilepsy patients. Method. Twenty drugnaïve patients (15 males and 5 females) with epilepsy, and an equal number of age and gender matched controls, were evaluated for short-term rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Evrengul et al (3) showed increase in the sympathetic control of the heart rate in newly diagnosed GTCS. From this center in another study, subtle cardiac autonomic dysfunction especially reduced vagal tone in patients with GTCS (22). Devinsky et al (2) found abnormal BP changes for autonomic tests in patients with CPS, which might indicate impaired baroreflex functions.…”
Section: Discussionmentioning
confidence: 83%
“…Evrengul et al (3) showed increase in the sympathetic control of the heart rate in newly diagnosed GTCS. From this center in another study, subtle cardiac autonomic dysfunction especially reduced vagal tone in patients with GTCS (22). Devinsky et al (2) found abnormal BP changes for autonomic tests in patients with CPS, which might indicate impaired baroreflex functions.…”
Section: Discussionmentioning
confidence: 83%
“…In adults with generalized epilepsy, the overall evidence indicates that HRV is also abnormal. Findings indicating an interictal shift toward sympathetic dominance have been reported for adult patients with juvenile myoclonic epilepsy and epilepsy with generalized tonic–clonic seizures; however, the degree of derangement tends to be milder than that observed with TLE. One study of a relatively small cohort of patients with drug‐naive genetic generalized epilepsy did not find statistically significant differences in HRV when compared to controls …”
Section: Interictal Hrv Patterns In Different Epilepsy Typesmentioning
confidence: 80%
“…[65] In another study at this center on drug-naïve new-onset 20 patients with epilepsy, subtle but definite cardiac autonomic dysfunction, especially in vagal tone, was identified. [66] Practice of yoga might have a role as an adjuvant therapy in the management of autonomic dysfunction in patients with refractory epilepsy. [67]…”
Section: Autonomic Changes In Epilepsymentioning
confidence: 99%